2014
DOI: 10.36884/jafm.7.04.21420
|View full text |Cite
|
Sign up to set email alerts
|

Applications of 2-D Moiré Deflectometry to Atmospheric Turbulence

Abstract: We report on applications of a moiré deflectometry to observations of anisotropy in the statistical properties of atmospheric turbulence. Specifically, combining the use of a telescope with moiré deflectometry allows enhanced sensitivity to fluctuations in the wave-front phase, which reflect fluctuations in the fluid density. Such phase fluctuations in the aperture of the telescope are imaged on the first grating of the moiré deflectometer, giving high spatial resolution. In particular, we have measured the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Various models are proposed to describe atmospheric turbulence based on the turbulence homogeneity and isotropy, and have been generalized to study the underwater one. Many studies have shown that the atmospheric turbulence [19,[29][30][31] as well as the underwater [32,33] are anisotropic. Recently, many papers have been published about the effects of anisotropic underwater turbulence on the optical communication systems [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Various models are proposed to describe atmospheric turbulence based on the turbulence homogeneity and isotropy, and have been generalized to study the underwater one. Many studies have shown that the atmospheric turbulence [19,[29][30][31] as well as the underwater [32,33] are anisotropic. Recently, many papers have been published about the effects of anisotropic underwater turbulence on the optical communication systems [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, contactless optical methods do not disturb the flow field. Due to the presence of density gradients, compressible fluid flow is very suitable for an investigation using optical methods that are sensitive either to the refractive index of the medium through which the light wave propagates (interferometry), or to a refractive index gradient in the medium (schlieren [7][8][9][10][11], shadowgraph [12][13][14][15][16], Moiré deflectometry [17][18][19][20][21]). Interferometric methods such as classical interferometry [22,23], holographic interferometry [24] and digital holographic interferometry [25][26][27][28][29] stand as the most accurate optical techniques [26,30,31] that are applied in many sectors of industry and scientific research, notably in the study of liquid cooling [32], diffusion [33], convection [34,35], temperature measurements and visualization [1,25,36], temperature fields measurement in pulsatile jets [25], studies of living cell imaging [37,38], precision measurement [15,39,40], vibrometry [41,42] etc.…”
Section: Introductionmentioning
confidence: 99%